Influence of stainless steel impact damper on tribological properties during boring process. (2021) - Lawrance, G.; Sam Paul, P.; Ezhil, M.; Ebi Ashish, J.; Gokul, R.; Subhash, M.
Abstract: Tool vibration is a major issue in boring process because of its overhanging length which affects its tribological properties. A suitable mechanism can reduce tool vibration and increase the tribological properties. In present investigation, a stainless steel impact damper on boring tool is developed and experiments were conducted to reduce tool vibration and improve tribological properties. The results were analyzed using signal to noise ratio method and it shows that stainless steel spheres in boring tool suppress tool vibration and enhance the tribological properties efficiently when it is compared with conventional boring tool.